2020
DOI: 10.1523/eneuro.0437-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Frontal, Parietal, and Temporal Brain Areas Are Differentially Activated When Disambiguating Potential Objects of Joint Attention

Abstract: This Early Release article has been peer-reviewed and accepted, but has not been through the composition and copyediting processes. The final version may differ slightly in style or formatting and will contain links to any extended data. Alerts: Sign up at www.eneuro.org/alerts to receive customized email alerts when the fully formatted version of this article is published. 1. Frontal, parietal and temporal brain areas are differentially activated when disambiguating potential objects of joint attention 2. Neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The latter notion gets further support from the massive bidirectional connections of the STS with a range of higher-order brain areas such as the ventral and medial frontal cortex, lateral prefrontal and premotor areas, the parietal cortex, and mesial temporal regions ( Seltzer and Pandya, 1989 , 1994 ), strategically placing it as a functional link between early visual areas and higher order areas. For example, integrating different modalities of information, such as vision and audition, is highly beneficial for disambiguating social decision processes ( Kraemer et al, 2020 ). Another example is facial expression recognition which builds upon the ability to combine biological motion and facial information ( Fisher and Freiwald, 2015 ).…”
Section: Visual Processing In the Sts And It Cortexmentioning
confidence: 99%
“…The latter notion gets further support from the massive bidirectional connections of the STS with a range of higher-order brain areas such as the ventral and medial frontal cortex, lateral prefrontal and premotor areas, the parietal cortex, and mesial temporal regions ( Seltzer and Pandya, 1989 , 1994 ), strategically placing it as a functional link between early visual areas and higher order areas. For example, integrating different modalities of information, such as vision and audition, is highly beneficial for disambiguating social decision processes ( Kraemer et al, 2020 ). Another example is facial expression recognition which builds upon the ability to combine biological motion and facial information ( Fisher and Freiwald, 2015 ).…”
Section: Visual Processing In the Sts And It Cortexmentioning
confidence: 99%
“…These areas were slightly more anterior than the gaze-following region of the posterior superior temporal sulcus identified in humans ( Materna et al, 2008 ; Marquardt et al, 2017 ) emphasizing the homologies between humans and non-human primates. More recently, Kraemer et al (2020) have shown that the human lateral intraparietal sulcus and the inferior frontal junction contribute spatial information to gaze following. While neuroimaging studies in humans can highlight the location of large groups of neurons that become active during gaze following, single neuron recording in humans and non-human primates can identify the specific contribution of the neurons in these areas to gaze following and joint attention.…”
Section: Discussionmentioning
confidence: 99%
“…The Gaze Following Patch (GFP) is a circumscribed region in the posterior part of the temporal cortex which was discovered in healthy human subjects that participated in fMRI experiments in which the task was to use the gaze direction of a demonstrator to identify a target object among distractors. 15 In contrast with the respective control condition, iris-color mapping in which the observer had to shift gaze to an object whose color corresponded to the color of the demonstrator’s iris, the gaze-following condition yielded a significantly larger BOLD response within the GFP. This preference for gaze direction suggests that the GFP might be the neural realization of Baron-Cohen’ ss Eye Direction Detector (EDD).…”
Section: Introductionmentioning
confidence: 95%